Women participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows four women participating in the 1986 y-Walk. They are walking on Almaden Boulevard and are probably crossing West San Fernando Street in a crosswalk. Some of the people are wearing tee shirts that read: "Walk for women. YWCA 1986." A traffic light is indicating that it is safe to walk and vehicles are passing by the participants in the street. The large white building in the background is probably the Hotel DeAnza.